Ecohydrological implications of aeolian sediment trapping by sparse vegetation in drylands. Issue 7 (30th May 2018) - Gonzales, Howell B.; Ravi, Sujith; Li, Junran; Sankey, Joel B.
Abstract: Aeolian processes are important drivers of ecosystem dynamics in drylands, and important feedbacks exist among aeolian—hydrological processes and vegetation. The trapping of wind‐borne sediments by vegetation canopies may result in changes in soil properties beneath the vegetation, which, in turn, can alter hydrological and biogeochemical processes. Despite the relevance of aeolian transport to ecosystem dynamics, the interactions between aeolian transport and vegetation in shaping dryland landscapes where sediment distribution is altered by relatively rapid changes in vegetation composition such as shrub encroachment, are not well understood. Here, we used a computational fluid dynamics modelling framework to investigate the sediment trapping efficiencies of vegetation canopies commonly found in a shrub‐grass ecotone in the Chihuahuan Desert (New Mexico, USA) and related the results to spatial heterogeneity in soil texture and infiltration measured in the field. The vegetation structures were created using a computer‐aided design software, with inherent canopy porosities, which were derived using Light Detection and Ranging (LiDAR) measurements of plant canopies. Results show that considerable heterogeneity in infiltration and soil grain size distribution exist between the microsites, with higher infiltration and coarser soil texture under shrubs. Numerical simulations further indicate that the differential trapping of canopies might contribute to the observed heterogeneity in soil texture. In the early stages of encroachment, the shrub canopies, by trapping coarser particles more efficiently, might maintain higher infiltration rates leading to faster development of the microsites with enhanced ecological productivity, which might provide positive feedbacks to shrub encroachment.